Hydrogen Abstraction from Fluorinated Ethyl Methyl Ether Systems by OH Radicals. (10th February 2016) - White, Curtis W.; Martell, Jaime M.
Abstract : A systematic computational investigation of hydrogen abstraction by OH from the full series of fluorinated ethyl methyl ethers (EME) containing at least one H and one F, C 2 H n X 5 - n O C H m X 3 - m (n = 0 – 5, m = 0 – 3 ; and n = m = 0 not allowed), including 147 reactants and 469 transition states, has been carried out, employing the MP2/6-31G(d) level of theory. Results for optimized geometries, including evidence of intramolecular hydrogen bonding in transition states, and barrier heights are presented. Trends pertaining to the number of fluorines substituted, key bond lengths, barrier heights, and key bond angles were found with good correlations and were investigated. An increase in the number of F increases the barrier height of the reaction. An increase in some parameters such as C–H length of TS, relative change in C–H from reactants to TS, ∠COC of reactants, ∠HOH in the TS, and relative change in ∠HOH between TS and free water bond angle also correlates with increased barrier height. An increase in other parameters like C–H length in the reactants and hydrogen bonding can decrease the barrier height.